PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, DAN KUALITAS AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BEI TAHUN 2016-2018 - Napitupulu, Theresia; Wulandari, Endang (JIM : Journal Of International Management, 2022)
One of the obligations of companies that have been listed on the Indonesia Stock Exchange is to publish financial reports that have been audited by a Public Accountant. The data used is the financial statements of companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sampling technique used is purposive sampling technique, namely determining the sample with certain criteria. Obtained a sample of 11 companies, so that the amount of data to be studied in this study was 33 data. The data analysis technique in this study uses descriptive test, classical assumption test, coefficient of determination test, multiple linear regression analysis, t test, and F test using the SPSS (Statistical Product and Service Solutions) version 25 program. From the table above, it is found that the sig value is 0.123> ? 0.05, so reject Ho, which means that the regression model is significant, which means that all variables consisting of company size, profitability, solvency, and audit quality together have no significant effect on Audit Delay. The results of this study found that company size, profitability, solvency, and audit quality have no significant effect on audit delay.